CURRENT UNDERSTANDING OF HYPERPOLARIZATION-ACTIVATED AND CYCLIC NUCLEOTIDE-GATED (HCN) CHANNELS: A REVIEW - ALOK , SINGH; VIVEK , KHARE (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Hyperpolarization-activated and Cyclic Nucleotide-gated (HCN) channels with significant physiological role are found to be present in heart and brain. These channels have got four subtypes encoded by four different genes. They play significant role in maintainance of cardiac rhythm and neuronal excitability with definite but partially defined role in development of arrhythmia, epilepsy and neuropathic pain. These are also known as pace maker channels. In present review we will mainly discuss electrophysiology of neurons and SA node in special reference to HCN channel. In the heart mainly HCN4 subtype is present while in brain all four isotype have been found where they are involved in numerous neuronal functions i.e. dendrite c integration, memory, thalamo-cortical rhythm etc. Further in review we will also discuss in brief the physiology and uniqueness of this ion channel and disorders especially epilepsy, neuropathic pain and cardiac arrhythmia, due to the malfunctioning of these ion channels. The newer possibilities of modifying this ion channel along with the drugs acting will also be discussed. Keywords: HCN ion channels, Arrythmia, Epilepsy, Neuropathic Pain.